2016
DOI: 10.1097/htr.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Posttraumatic Amnesia Predicts Neuropsychological and Global Outcome in Complicated Mild Traumatic Brain Injury

Abstract: Objectives Examine the effects of post-traumatic amnesia (PTA) duration on neuropsychological and global recovery from 1 to 6 months after complicated mild traumatic brain injury (cmTBI). Participants 330 persons with cmTBI defined as Glasgow Coma Scale score of 13–15 in Emergency Department, with well-defined abnormalities on neuroimaging. Methods Enrollment within 24 hours of injury with follow-up at 1, 3, and 6 months. Measures Glasgow Outcome Scale-Extended, California Verbal Learning Test II, Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
1
13
0
3
Order By: Relevance
“…This study adds to the literature supporting the hypothesis that prolonged PTA duration significantly increases the burden of care (1013, 36, 37) and this burden of care continues to affect patients up to 5 years post-injury. Individuals with esPTA show lower FIM total scores at each time point from rehabilitation admission to 5 years post-injury compared to those without esPTA.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This study adds to the literature supporting the hypothesis that prolonged PTA duration significantly increases the burden of care (1013, 36, 37) and this burden of care continues to affect patients up to 5 years post-injury. Individuals with esPTA show lower FIM total scores at each time point from rehabilitation admission to 5 years post-injury compared to those without esPTA.…”
Section: Discussionmentioning
confidence: 60%
“…The cognitive sequelae following TBI often includes post-traumatic amnesia (PTA) characterized by disorientation, confusion, restlessness, inability to recall events, poor attention, and agitated behavior (69). In individuals with complicated mild TBI, Hart et al found that shorter PTA duration (≤1 week) predicted greater cognitive performance and less disability at 6 months post-injury vs. patients with a PTA duration >1 week (10). Eastvold et al used PTA duration as a predictor for outcomes after TBI and found that patients with PTA <30 days were more than three times as likely to be living independently 1 year after injury when compared to patients with PTA duration >30 days (11).…”
Section: Introductionmentioning
confidence: 99%
“…The predictive value of GCS has been found to be modest (9, 22). PTA duration greater than 7 days was found to be predictive of residual moderate disability at 6 months postinjury in patients with complicated MTBI (i.e., intracranial injuries) (23). Adding to the heterogeneity, imaging studies have demonstrated that brain pathology, as indicated by CT, is not a strong predictor of outcome with regard to symptoms or global function according to the GOSE in MTBI (11, 2426).…”
Section: Introductionmentioning
confidence: 99%
“…This might explain why primary brain injury by initial GCS poorly predicts cognitive outcome and HRQoL in this study. The duration of post‐traumatic amnesia may be a more valid predictor of global outcome than GCS 15 . Unfortunately, we had no data on post‐traumatic amnesia in our cohort.…”
Section: Discussionmentioning
confidence: 94%
“…Prolonged delirium constitutes a risk for long‐term cognitive impairment after the ICU stay, 6 though this association was not found in a recent Danish cohort study 2 . Furthermore, prolonged post‐traumatic amnesia (PTA) in survivors of traumatic brain injury (TBI) is associated with poor cognitive outcomes 15 and development of dementia 16 . PTA is a memory disorder, often with symptoms such as disorientation, confusion and behavioural symptoms overlapping with the definition of delirium 17,18 .…”
Section: Introductionmentioning
confidence: 99%